Aggregation of magnetic nanoparticles in biological solvents evaluated by HTS-SQUID magnetic immunoassay system - Yamashita, Kei; Kishimoto, Kouhei; Kuroda, Hiroto; Wang, Jin; Sakai, Kenji; Mohd Mawardi, Saari; Kiwa, Toshihiko (Institute of Electrical and Electronics Engineers Inc., 2023)
Magnetic nanoparticles (MNPs) have been studied for various medical applications by taking advantage of their unique magnetic properties. Magnetic immunoassay (MIA) is a technique for the rapid detection of target biomarkers by antigen-antibody reaction between antibody-modified MNPs and the target biomarker. In this study, we aim to improve the accuracy of the MIA, we evaluated the AC magnetic properties of MNPs in the biological solvents. To measure the magnetic signal of MNPs, we used the developed HTS-SQUID magnetic immunoassay system. First, we evaluated the instability of the HTS-SQUID magnetic immunoassay system using pellets of manganese (II) fluoride. The results show that the device instability due to operating time does not affect the measurement of magnetic signal changes in MNPs due to biological solvents. Since the magnetic properties of MNPs depend on particle size and viscosity, we measured the time evolution of the magnetic signal of Resovist in glycerin, human serum, sheep whole blood, and NaCl. It was found that the magnetic signal of Resovist decreased exponentially with ions contained in the solvent. The results are fitted as the exponential double function, suggesting that the magnetic signal of MNPs in biological solvents is affected by the aggregation of MNPs in the blood and that there are at least two steps in the mechanism of the aggregation.